Urgensi Kecerdasan Emosional dalam Menerapkan Model Pembelajaran Demokratis oleh Guru di Era Digital - Safatulus Giawa; Arozatulo Telaumbanua (TEVUNAH: Jurnal Teologi dan Pendidikan Kristen, 2023)
This article discusses Christian education's challenges in the digital era, particularly in implementing democratic learning models. The study aims to solve these challenges by analysing existing research on emotional intelligence in teachers. The article suggests that teachers must be emotionally intelligent to create a comfortable learning environment for students. The study recommends that teachers be aware of their role in national education and strive to improve their emotional intelligence to apply democratic learning models in the digital era. The article concludes that when teachers understand their role well, education in both online and onsite formats can continue to achieve national education goals.